THE ROLE OF HORMONAL AND NON-HORMONAL MARKERS IN ASSESSING PERINATAL STRESS AND ITS CLINICAL IMPLICATIONS - Daniel Chołuj; Wiktor Śliwiński; Jakub Marciniak; Jakub Mazur; Mateusz Kosowski; Weronika Pura; Karolina Zarówna; Dominika Matecka (International Journal of Innovative Technologies in Social Science, 2026)
Background: Prenatal and perinatal stress activates the maternal and fetal HPA axis, releasing biomarkers that can cross the placenta. In high concentrations, these substances may lead to congenital malformations, preterm labor, or intrauterine growth restriction (IUGR). Despite their potential, endogenous biomarkers are not yet part of standard gynecological diagnostics. Aim: This paper analyzes recent reports on hormonal and non-hormonal perinatal stress biomarkers to evaluate their application in assessing health risks for mothers and fetuses. Material and Methods: This literature review examines clinical trials and observational studies from the late 20th and early 21st centuries. It focuses on laboratory techniques such as ELI-SA, HPLC, and radioimmunoassay used to measure stress markers in maternal serum, cord blood, amniotic fluid, and urine. Results: Studies show that copeptin levels rise significantly during fetal hypoxia and IUGR, aiding ultrasonographic differentiation. Maternal cortisol levels correlate negatively with birth weight and increase the risk of infants being small for gestational age (SGA). ACTH and CRH serve as indicators of HPA axis maturity and predictors of preterm birth. Regarding non-hormonal markers, malondialdehyde and 8-isoprostane are sensitive indicators of oxidative stress linked to preeclampsia. Furthermore, elevated proinflammatory cytokines (IL-1, IL-6, IL-8, TNF-alpha) are closely associated with intrauterine infections and the onset of preterm labor. Conclusions: Perinatal stress biomarkers offer significant prognostic value for identifying risks of preterm labor and developmental pathologies. While cortisol currently has the greatest clinical utility, copeptin and malondialdehyde are noted for their stability and potential for routine screening. Further clinical trials are necessary to integrate these markers into standard obstetric care.